Economic feasibility of localization of production in consumer countries: assessment of risks and benefits for small and medium-sized enterprises - Khalamandro, Mykhaylo (Global Prosperity, 2025)
Abstract. The relevance of the study is stipulated by the need to find adaptive mechanisms for organizing production in the context of the transformation of global value chains, disruption of supply sustainability and increasing institutional fragmentation of world trade. The modern economy is focusing on localized models that reduce vulnerability to external shocks and reduce logistics costs. For small and medium-sized enterprises (SMEs), localization is not only a strategic choice, but also a tool for ensuring operational flexibility in the regional context. The purpose of the study is to substantiate the economic feasibility of localizing production in consumer countries, taking into account the specifics of SMEs, as well as to formulate recommendations for reducing risks and improving the efficiency of localized models in times of global instability. The research methodology is based on a combination of institutional analysis, elements of the comparative approach, and systematization of data from analytical reports and cases of localization of production in SMEs. To structure the types of localized models, elements of qualitative content analysis were used, taking into account industry and regional specifics. The study revealed that the key factors of localization efficiency are regulatory fragmentation, shortage of production resources, and limited access to local markets and logistics clusters. The article analyzes how industry specifics, the level of digital maturity of an enterprise and the type of its organizational structure determine the configuration of implementation of localized strategies in the practice of SMEs. It is found that enterprises with different market focuses demonstrate heterogeneity in approaches to adapting management, using digital solutions, and interacting with the local environment. The conclusions show that effective localization for SMEs does not imply a unified transfer of capacities, but rather the construction of a multi-level strategy that integrates digital tools, flexible organizational formats, and partnership models at the local level. Prospects for further research are related to quantifying the impact of localization on the operational sustainability of SMEs in different regional contexts, developing indicators of localization readiness, and analyzing the role of digital infrastructure in scaling regional production networks.